Striking a balance with big data - Omoola, Sodiq (New Straits Times Press (M) Bhd, 2019)
In Malaysia, the promotion of the big data analytic ecosystem is under the purview of the Malaysia Digital Economy Corporation (MDec) which seeks to harness foreign and domestic potentials of the digital economy. The agency has also implemented programmes on awareness and adoption of big data and supported data science in the academic curriculum in Malaysia.